Polymer-mediated crystallisation of proteins - Zhu, Jing (2015)
Proteins are the functional machines of nature and play an essential role in life. Understanding the structure and function of proteins is central to numerous areas of science and technology, including biotechnological, pharmaceutical and chemical industries. Protein crystals are an important objective for many researchers, but even though there are many examples of protein crystals reported, there are still many uncertainties in controlling the crystallisation process. In addition, while protein crystals have mostly been obtained for characterisation purposes, there are other applications where defined assemblies of proteins, either crystals or self-assembled protein nanoparticles, are desirable. These include industrial biocatalysis, therapeutic protein formulations, and even energy-harvesting systems. Accordingly, there remains a high demand for well-defined protein crystals or nanoscale aggregates. A variety of techniques have been used to produce protein crystals, the typical strategy involves the addition of nucleants surface, or surface-active materials into the crystallisation solution. Solution ‘additives’ of diverse types have proven crucial in the control of protein crystallisation. These additives can act via multiple roles in a crystallisation process, such as by enhancing intermolecular contacts between protein macromolecules, or disrupting unfavourable intermolecular association, or diminishing interactions between protein and solvent. Synthetic polymers are important additives for protein crystallisation control as there are many possible chemistries which can be introduced into the backbone and side-chains, giving a very wide range of functional behavior. However, because there are so many factors which can affect crystallisation, many of which are still poorly understood, to date only a very few classes of polymers have been studied as additives for protein crystallisation. Moreover, the mechanisms governing their interactions with protein crystals or surrounding solvent are elusive. In the study presented here, we show that polymers designed with varying degrees of charge, molecular weight and backbone structure influenced the crystallisation of three target proteins: hen-egg white lysozyme (HEWL); concanavalin A (Con A); and bovine liver catalase (BLC). Polymers were prepared as ‘additives’ into protein solution to influence the proteins crystallisation process, leading to changes in size, habit, morphology and even polymorph of the final crystals. A simple model linking polymer structure and charge to protein isoelectric point (pI) and crystallisation rate is proposed.